PENGARUH PELATIHAN DAN ORIENTASI KEWIRAUSAHAAN INDIVIDU TERHADAP MINAT USAHA YANG DIMEDIASI OLEH EFIKASI DIRI PADA UMKM DI KOTA TANGGERANG - Mia Rahmawati; C. Zurnali (LPPM STAI Muhammadiyah Probolinggo, 2026)
The growth in the number of MSMEs in Tangerang City has not been matched by adequate entrepreneurial quality, as high initial interest in starting a business is often hindered by psychological doubts and a lack of courage to take action. This study aims to evaluate the role of Self-Efficacy in mediating the influence of Training and Individual Entrepreneurial Orientation on the escalation of Entrepreneurial Interest. An explanatory quantitative approach was used through a survey and purposive sampling of 100 MSME entrepreneurs in Tangerang City, with data analysis conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM). Empirical results demonstrate that Training (β=0.494; p=0.000) and Individual Entrepreneurial Orientation (β=0.403; p=0.000) have a positive and significant effect on Self-Efficacy. A crucial finding confirms that Self-Efficacy operates as the most dominant predictor of Business Interest (β=0.654; p=0.000), while also serving as a robust partial mediator for Training (β indirect=0.323) and Entrepreneurial Orientation (β indirect=0.263). This structural model demonstrates strong predictive power, explaining 71.8% of the variance in Entrepreneurial Interest (R²=0.718). As a concrete recommendation, local governments are advised to immediately redesign training curricula from a mere transfer of cognitive knowledge to a self-efficacy building approach (mental resilience simulation) in order to convert latent intentions into real business actions.